Resilience and stress management amongst corporate security managers: a hybrid approach to thematic analysis. Issue 2 (12th February 2021) - Rahman, Sami; Cachia, Moira
Abstract : Purpose: The purpose of this study is to examine the experience of stress by national corporate security managers in the United Kingdom and how they manage it. Design/methodology/approach: A qualitative approach was adopted where in-depth semi-structured one-to-one interviews with 22 male participants were conducted as the method of data collection. This was analysed using hybrid thematic analysis. Findings: Three overarching themes were elicited, namely: "Resilience", "Synergy" and "Work/life balance". The outcome showed that stress management by security managers is moulded by an interaction of various facets, with an emphasis on "resilience" having 66% of content occurrence, a factor which complements and enriches the job demand–control-support (JDCS) theoretical framework (Johnson and Hall, 1988). Practical implications: The paper argues the importance of the interaction between resilience and the dimensions of the JDCS. The research indicates the interaction is important in how practitioners can develop interventions in reducing stress in the workplace. Social implications: This research outcome implies that employees in managerial positions should be provided with resilience assessment and training to enhance their job effectiveness and well-being. Resilience needs to be recognised as an important trainable skill and stress management training should emphasise the enhancement of resilience. Originality/value: This type of qualitative investigation on the lived experiences of stress management and how this affected one's resilience's in a high-stress industry is innovative as past research is mostly quantitative.